An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California - Rouse, Greg W.; Goffredi, Shana K.; Johnson, Shannon B.; Vrijenhoek, Robert C. (Zootaxa, 2018)
We incorporate DNA sequences from a comprehensive sampling of taxa to provide an updated phylogeny of Osedax and discuss the remarkable diversity of this clade of siboglinids. We formally describe 14 new species of Osedax from Monterey Bay, California, USA, raising the total number of properly named Osedax species to 25. These new species had formerly been recognized by informal names in various publications, and on GenBank. The descriptions document the occurrence of dwarf males in five of the new species. The distribution for the 19 species of Osedax known to occur in Monterey Bay across depths from 385 to 2898 meters and various bone substrates is documented. The exploitation of extant bird and marine turtle bones by Osedax is reported for the first time.